Croatia – the path from Yugoslavia to the EU – Future: Success or wash-out? - Borbély, Tamás (Acta Agraria Debreceniensis, 2015)
Croatia joined to the European Union as the 28th member state on June the 1th 2013. With this it became the second ex-yugoslavian country to be part of the European elite. Croatia’s long road from being part of a socialist state conglomerate to become the newest member of the EU was not just winding but often and still it is shaky.